Microscopic Colitis: A Key Differential Diagnosis in Chronic Watery Diarrhea - Klimczak, Adrianna; Pietrzak, Barbara; Patelski, Mikołaj; Czapla, Maciej; Surma, Mateusz; Molenda, Jakub; Kuczma, Matylda; Kotlarz, Wiktoria; Mikusek, Wiktoria; Kamińska, Marta; Dobrzeniecki, Krzysztof (Quality in Sport, 2025)
INTRODUCTION Microscopic colitis (MC) is an often-overlooked inflammatory disorder of the colon. It presents with persistent, non-bloody, watery diarrhea. The characteristic of the condition is a lack of visible endoscopic abnormalities. It includes two main histological forms: collagenous colitis and lymphocytic colitis. While it mostly affects older individuals, MC is often missed in clinical practice, resulting in prolonged symptoms and excessive diagnostic procedures. AIM OF THE STUDY This review aims to present current knowledge of microscopic colitis. We summarize its key symptoms, clinical manifestations, diagnostic methods, and available therapies. The goal of this study is to understand this disease better and demonstrate why early detection and accurate diagnosis are important. MATERIALS AND METHODS A structured literature search was performed in PubMed and Google Scholar to identify relevant studies on MC. We focused on diagnostic methods and therapy possibilities. The search included relevant keywords and Medical Subject Headings (MeSH). Supplementary articles were included through manual review of the reference lists from key publications. CONCLUSION Microscopic colitis can be treated. Unfortunately, it is often underdiagnosed as a cause of chronic diarrhea in adults. Once you identify it quickly and confirm the disorder with histological samples, you can initiate effective treatment, usually with budesonide. Early recognition can minimize unnecessary, often expensive, testing and patient suffering. Ongoing follow-up may be necessary in cases with frequent relapse.